2019
DOI: 10.1186/s12915-018-0621-5
|View full text |Cite
|
Sign up to set email alerts
|

Thawing out frozen metabolic accidents

Abstract: Photosynthesis and nitrogen fixation became evolutionarily immutable as “frozen metabolic accidents” because multiple interactions between the proteins and protein complexes involved led to their co-evolution in modules. This has impeded their adaptation to an oxidizing atmosphere, and reconfiguration now requires modification or replacement of whole modules, using either natural modules from exotic species or non-natural proteins with similar interaction potential. Ultimately, the relevant complexes might be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…Why are nucleobases built from amino acids and not by oligomerization of HCN? It is not yet clear whether the answers to these questions lie in chance “frozen accidents” of prebiotic chemistry that were too difficult to displace in a complex system , or whether they became ubiquitous due to convergence toward an optimal chemical solution . It could well be that the processes by which life makes and breaks down its transient metabolic intermediates are just as fundamental to its nature and origin as RNA or cellular compartments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why are nucleobases built from amino acids and not by oligomerization of HCN? It is not yet clear whether the answers to these questions lie in chance “frozen accidents” of prebiotic chemistry that were too difficult to displace in a complex system , or whether they became ubiquitous due to convergence toward an optimal chemical solution . It could well be that the processes by which life makes and breaks down its transient metabolic intermediates are just as fundamental to its nature and origin as RNA or cellular compartments.…”
Section: Introductionmentioning
confidence: 99%
“…There is historical evidence that it is hard to transition to a fundamentally different reaction network; life has not ever done it as far back as we have evidence. Evolutionary biologists might describe this phenomenon as a “frozen metabolic accident”, , a variation of the “frozen accident” term historically coined by Crick to describe the universality of the genetic code . In short, once a (bio)­chemical system begins to harbor multiple connected subsystems, it becomes essentially unalterable because a significant change would reverberate through all interconnected subsystems.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial redesign of the light reactions of photosynthesis has not been attempted yet, although reconstruction of some photosynthetic modules in prokaryotes, such as biosynthesis of carotenoids and Chl, as well as RuBisCO (Aigner et al., 2017; Chen et al., 2018; Sandmann et al., 1999), provide a good basis for further progress. The tailoring of the light reactions of plant photosynthesis has been limited to a few instances of trial‐and‐error experiments, overproducing components of the light reactions or auxiliary proteins associated with the photosynthetic apparatus (for review, see Leister 2019a).…”
Section: Strategies For Enhancing Photosynthesis and Their Limitationsmentioning
confidence: 99%
“…Overproduction of single photosynthetic proteins has been reported to enhance plant photosynthesis (for review, see Leister 2019a), although it is unclear whether the reported enhancements hold true under field conditions. More recently, nuclear overproduction of the plastid‐encoded D1 protein was reported to enhance both stress resistance and crop yield under field conditions (Chen et al., 2020).…”
Section: Strategies For Enhancing Photosynthesis and Their Limitationsmentioning
confidence: 99%
“…Due to several issues associated with the C3 pathway, the maximum photosynthesis rates commonly observed among C3 species are generally lower than those of C4 ones. Although the core mechanisms of photosynthesis are highly conserved [13,14], natural variation in photosynthesis rates has been observed for major crops such as wheat [15], rice [16,17], maize [18], soybean [19], sorghum [20], as well as for the model species Arabidopsis thaliana [21,22]. Much higher levels of variation can be expected in other species that are more ecologically specialized [23].…”
Section: Introductionmentioning
confidence: 99%